The Pragmatic Power and Promise of Theoretical Environmental Ethics: Forging a New Discourse. (1st February 2002) - Callicott, J.B.
Abstract : Pragmatist environmental philosophers have (erroneously) assumed that environmental ethics has made little impact on environmental policy because environmental ethics has been absorbed with arcane theoretical controversies, mostly centred on the question of intrinsic value in nature. Positions on this question generate the allegedly divisive categories of anthropocentrism/nonanthropocentrism, shallow/deep ecology, and individualism/holism. The locus classicus for the objectivist concept of intrinsic value is traceable to Kant, and modifications of the Kantian form of ethical theory terminate in biocentrism. A subjectivist approach to the affirmation of intrinsic value in nature has also been explored. Because of the academic debate about intrinsic value in nature, the concept of intrinsic value in nature has begun to penetrate and reshape the discourse of environmental activists and environmental agency personnel. In environmental ethics, the concept of intrinsic value in nature functions similarly to way the concept of human rights functions in social ethics. Human rights has had enormous pragmatic efficacy in social ethics and policy. The prospective adoption of the Earth Charter by the General Assembly of the United Nations may have an impact on governmental environmental policy and performance similar to the impact on governmental social policy and behaviour of the adoption by the same body in 1948 of the Universal Declaration of Human Rights. Belatedly, but at last, the most strident Pragmatist critics of the concept of intrinsic value in nature now acknowledge its pragmatic power and promise.